The Creative Urban Diaspora Economy: A Disparity Analysis among Migrant Entrepreneurs - Karima Kourtit; Peter Nijkamp; Daniel Arribas-Bel (Tinbergen Institute, 2013)
This paper highlights the `magic of diasporas' - as a source of progress in a globalizing world - with special attention for migrant (or ethnic) entrepreneurship. The present study aims to identify and examine the critical critical success factors of migrant enterprises and their socio-economic implications in modern cities. We will assess the business performance of migrant entrepreneurs by employing a new analytical instrument, coined Super-Efficient Data Envelopment Analysis (Super-DEA). Next, we will offer a multidimensional visualization of the relative differences in the performance of migrant entrepreneurs by introducing a recently developed technique from the cognitive sciences, coined Self-Organizing Maps (SOMs). This analytical apparatus will be tested on the basis of a sample of Moroccan entrepreneurs in four Dutch cities, namely Amsterdam, Rotterdam, The Hague and Utrecht. The study will be concluded with some strategic conclusions.
Keywords: L26; O15; 330; migrant entrepreneurship; diaspora economy; ethnic diversity; foreign migrants; economic performance; social capital; immigrant networks; social networks; Super-Efficient Data Envelopment Analysis; Self-Organizing Maps; SWOT analysis